2016
DOI: 10.3390/ijms17091472
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Large Seeds from Three Different Medicago truncatula Ecotypes Reveals a Potential Role of Hormonal Balance in Final Size Determination of Legume Grains

Abstract: Legume seeds are important as protein and oil source for human diet. Understanding how their final seed size is determined is crucial to improve crop yield. In this study, we analyzed seed development of three accessions of the model legume, Medicago truncatula, displaying contrasted seed size. By comparing two large seed accessions to the reference accession A17, we described mechanisms associated with large seed size determination and potential factors modulating the final seed size. We observed that early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…These DELLA proteins were found to be differentially expressed during fruit development in Arabidopsis [56]. Studies of GA action are mostly limited to seed germination and plant growth although it has been hypothesized that it could be among the phytohormones that could, combined with auxin and ABA, control the final seed size in the Medicago model plant [57]. The role of GA in cell division and elongation has been established [58].…”
Section: Candidate Genes Associated With Seed Size Are Found In the Qmentioning
confidence: 99%
“…These DELLA proteins were found to be differentially expressed during fruit development in Arabidopsis [56]. Studies of GA action are mostly limited to seed germination and plant growth although it has been hypothesized that it could be among the phytohormones that could, combined with auxin and ABA, control the final seed size in the Medicago model plant [57]. The role of GA in cell division and elongation has been established [58].…”
Section: Candidate Genes Associated With Seed Size Are Found In the Qmentioning
confidence: 99%
“…Seed size in barrel medic and Arabidopsis has also been shown to be determined by the activity of cellular events during early stages of seed development, which in turn are regulated by set ratios between ABA and IAA (Bandyopadhyay et al 2016;Raz et al 2001;Schruff et al 2006). Previous research in Arabidopsis has also shown the role of members of the cytochrome P450 CYP78A gene family in regulating organ size including seed size (Anastasiou et al 2007;Fang et al 2012).…”
Section: Seed Size and Weightmentioning
confidence: 99%
“…The following rounds of cell division are, apparently, less restricted in their number and duration and thus may serve as the source of temporal plasticity. Since in eudicots the initial number of cotyledon cells contributes mostly to the final seed size [48], the dimensional seed characteristics and developmental timing are often tightly interconnected to the point of correlation [49], the latter having been observed in Vicia faba (broad bean) [50], Medicago truncatula (barrel medic) [51], and P. sativum [52]. [53,54].…”
Section: Cell Proliferation During Embryogenesismentioning
confidence: 99%
“…Cytokinin was shown to accumulate during embryo development in P. sativum, predominantly in the form of cis-isomers, and promote embryo growth [74]. Moreover, the elevated levels of isopentenyl riboside were found to accumulate during the embryo cell proliferation in accessions of M. truncatula with the prolonged pre-storage duration [51].…”
Section: Cell Proliferation During Embryogenesismentioning
confidence: 99%